Descriptive Analysis of PT Default Cases Aneka Tambag VS Phillip Philip Tonggoredjo and Its Correlation With Subekti's Default Theory - Pandan Winoto, Taufik (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is qualitative research with a descriptive approach. The data used in this research is secondary data that researchers obtained from books, scientific articles, credible websites, and other things that are usually used in every research. The data used in this research was analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions in descriptive form. The result in this article show that the PT Default Case. Aneka Tambang and Phillip Taonggoredjo which have been formulated by Subekti both in terms of their meaning, elements, types of causes, and other things because there was a non-fulfillment of the agreement by PT. Various mines whether carried out intentionally or through negligence. Keywords : Default Cases, Subekti, Theory